Gentrifier? Who, Me? Interrogating the Gentrifier in the Mirror. (30th July 2013) - Schlichtman, John Joe; Patch, Jason
Abstract Schlichtman and Patch suggest that there is an elephant sitting in the academic corner: while urbanists often use 'gentrification' as a pejorative term in formal and informal academic conversation, many urbanists are gentrifiers themselves. Even though urbanists have this firsthand experience with the process, this familiarity makes little impact on scholarly debate. There is, Schlichtman and Patch argue, an artificial distance in accounts of gentrification because researchers have not adequately examined their own relationship to the process. Utilizing a simple diagnostic tool that includes ten common aspects of gentrification, they compose two autoethnographic memoirs to begin this dialogue.